Sunlight assisted degradation of dye molecules and reduction of toxic Cr(VI) in aqueous medium using magnetically recoverable Fe3O4/reduced graphene oxide nanocomposite - Boruah, Purna K.; Borthakur, Priyakshree; Darabdhara, Gitashree; Kamaja, Chaitanya Krishna; Karbhal, Indrapal; Shelke, Manjusha V.; Phukan, Pallabi; Saikia, Dulen; Das, Manash R. (RSC Advances, 2016)
In view of the significant impact of magnetically recoverable catalysts in photocatalytic applications, Fe3O4/reduced graphene oxide (rGO) nanocomposite photocatalyst was synthesized by adopting an eco-friendly solution chemistry approach and has been characterized by high resolution transmission electron microscopy (HRTEM), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Fe3O4/rGO nanocomposite is efficiently utilized towards photocatalytic degradation of carcinogenic and mutagenic cationic as well as anionic dye molecules namely methyl green (MG), methyl blue (MB) and rhodamine B (RhB) under direct sunlight irradiation. The Fe3O4/rGO nanocomposite also demonstrated excellent photocatalytic reduction of aqueous Cr(VI) solution to nontoxic aqueous Cr(III) solution of more than 96% within 25 min under sunlight irradiation. Moreover, reusability of the magnetically recovered photocatalyst was studied efficiently up to 10 cycles in the degradation process. The catalyst was also characterized after the degradation of the dye molecule and the particle size of the Fe3O4 nanoparticles on the rGO sheets remained unchanged. The present investigation focuses on the importance of the use of Fe3O4/rGO nanocomposite towards photocatalytic degradation of waste water containing organic dye pollutants and toxic Cr(VI), as an easily recoverable and reusable photocatalyst with potential for many environmental remediation applications.

Ammonia-modified graphene sheets decorated with magnetic Fe3O4 nanoparticles for the photocatalytic and photo-Fenton degradation of phenolic compounds under sunlight irradiation - Boruah, Purna K.; Sharma, Bhagyasmeeta; Karbhal, Indrapal; Shelke, Manjusha V.; Das, Manash R. (Journal of hazardous materials, 2017)
Synthesis of easily separable and eco-friendly efficient catalyst with both photocatalytic and photo-Fenton degradation properties is of great importance for environment remediation application. Herein, ammonia-modified graphene (AG) sheets decorated with Fe3O4 nanoparticles (AG/Fe3O4) as a magnetically recoverable photocatalyst by a simple in situ solution chemistry approach. First, we have functionalized graphene oxide (GO) sheets by amide functional group and then Fe3O4 nanoparticles (NPs) are doped onto the functionalized GO surface. The AG/Fe3O4 nanocomposite showed efficient photocatalytic activity towards degradation of phenol (92.43%), 2-nitrophenol (2-NP) (98%) and 2-chlorophenol (2-CP) (97.15%) within 70–120 min. Consequently, in case of photo-Fenton degradation phenomenon, 93.56% phenol, 98.76% 2-NP and 98.06% of 2-CP degradation were achieved within 50–80 min using AG/Fe3O4 nanocomposite under sunlight irradiation. The synergistic effect between amide functionalized graphene and Fe3O4 nanoparticles (NPs) enhances the photocatalytic activity by preventing the recombination rate of electron-hole-pair in Fe3O4 NPs. Furthermore, the remarkable reusability of the AG/Fe3O4 nanocomposite was observed up to ten cycles during the photocatalytic degradation of these phenolic compounds.

Hexagonal boron nitride quantum dots embedded on layer-by-layer films for peroxidase-assisted colorimetric detection of β-galactosidase producing pathogens - Majumdar, Sristi; Gogoi, Devipriya; Boruah, Purna K.; Thakur, Ashutosh; Sarmah, Priyakhee; Gogoi, Parishmita; Sarkar, Sanjib; Pachani, Priyakshi; Manna, Prasenjit; Saikia, Ratul; Chaturvedi, Vikash; Shelke, Manjusha V.; et al. (ACS Applied Materials and Interfaces, 2024)
Pathogen detection has become a major research area all over the world for water quality surveillance and microbial risk assessment. Therefore, designing simple and sensitive detection kits plays a key role in envisaging and evaluating the risk of disease outbreaks and providing quality healthcare settings. Herein, we have designed a facile and low-cost colorimetric sensing strategy for the selective and sensitive determination of beta-galactosidase producing pathogens. The hexagonal boron nitride quantum dots (h-BN QDs) were established as a nanozyme that showed prominent peroxidase-like activity, which catalyzes 3,3 `,5,5 `-tetramethylbenzidine (TMB) oxidation by H2O2. The h-BN QDs were embedded on a layer-by-layer assembled agarose biopolymer. The beta-galactosidase enzyme partially degrades beta-1,4 glycosidic bonds of agarose polymer, resulting in accessibility of h-BN QDs on the solid surface. This assay can be conveniently conducted and analyzed by monitoring the blue color formation due to TMB oxidation within 30 min. The nanocomposite was stable for more than 90 days and was showing TMB oxidation after incubating it with Escherichia coli (E. coli). The limit of detection was calculated to be 1.8 x 10(6) and 1.5 x 10(6) CFU/mL for E. coli and Klebsiella pneumonia (K. pneumonia), respectively. Furthermore, this novel sensing approach is an attractive platform that was successfully applied to detect E. coli in spiked water samples and other food products with good accuracy, indicating its practical applicability for the detection of pathogens in real samples.
Keywords: biopolymer; colorimetric; h-BN quantum dots; nanozyme; pathogens; Sensor